LASER THERAPY FOR MANAGEMENT OF CEREBRAL DYSFUNCTION IN CASES OF ACUTE SEVERE PANCREATITIS - A. P. Vlasov; D. Y. Timoshkin; M. A. Spirina; I. A. Chigakova; T. I. Vlasova; T. A. Muratova (Неотложная медицинская помощь, 2018)
Background. A persistently high mortality rate of patients with pancreatitis is the result of multiple organ failure which is in many aspects associated with developing endogenous intoxication. Pancreatic encephalopathy is one of particular manifestations of this syndrome.Aim of study: to determine severity of cerebral dysfunction in cases of acute destructive pancreatitis, to assess the efficacy of laser therapy for this disease.Material and methods: The research is based on the results of clinical studies, carried out at the Republican Clinical Hospital No.3. Clinical laboratory analysis of 60 patients was conducted. The patients were randomly split into two equal groups: the comparison group (standard therapy) and the basic group (standard therapy and laser therapy). The patients were examined upon admission to hospital and in dynamics (day 1, 3, 5, and 7). The severity of cerebral dysfunction was assessed within controlled terms with the help of RASS and psychometric tests: number connection tests (A and B), “Point in circle”, “Labyrinth”, test of symbols and numbers. The level of endogenous intoxication was evaluated by the amount of hydrophilic (middle molecules) and hydrophobic (common and effective albumin concentration) component.Results. Acute severe pancreatitis led to a marked endogenous intoxication, which manifested itself as an increase in medium molecular weight peptides, decrease in common and effective albumin concentration, growth of toxicity index with regard to normal indices. During all research period the basic group (laser therapy) there was a decrease in medium molecular weight peptides, significant increase in common and effective albumin concentration and a decrease in index toxicity. Psychometric tests revealed a number of deviations from normal indices. At the beginning of the research, a reliable prolongation of time interval during examination tests (the number connection test B, “point in circle”, “Labyrinth”) was noted, and less cells were filled during symbol and number test with regard to normal indices. The subsequent analysis of psychometric tests of patients from the basic group revealed a shortening of time interval during number connection test block B, “Point in circle” and “Labyrinth”. More filled cells during symbol and numbers test were also observed.Conclusion. Results of psychometric tests confirmed latent encephalopathy during endogenous intoxication, associated with acute severe pancreatitis. The laser therapy as a component of complex treatment promotes to decrease severity of endogenous intoxication and manifestation of encephalopathy.